Baltų-slavų-tocharų leksikos gretybės („gyvūnų pavadinimų“ leksinė-semantinė grupė) - Miliūtė-Chomičenkienė, Aleta (Baltistica, 1990)
ETYMOLOGICAL PARALLELS IN BALTIC, SLAVIC AND TOCHARIAN IN “NAMES OF ANIMALS AND THEIR BODY PARTS” In this paper words which in Tocharian name animals and their body parts are analyzed. There are 13 words, which have etymological parallels in Baltic, Slavic and other Indo-European languages. Five words (from 13) which name domestic animals (Toch. A yuk, В yakwe, Lith. ašva; Toch. AB ku “bitch, dog”, Lith. šuo; toch. A ko, B ki, kew “cow”, Latv. guovs “ox”; Toch. A kayurs, B kaurse “bull”, Lith. veršis “calf”, Toch. В suwo “sow”, Latv. suvens “pig”) have retained many of the most archaic features of the Indo-European vocabulary. The remaining eight words, which name birds, beasts, fish and insects, frequently are derivatives from Indo-European verbal or adjectivel roots.